Liver X receptor activation protects against inflammation and enhances autophagy in myocardium of neonatal mouse challenged by lipopolysaccharides. Issue 9 (2nd September 2014) - Liu, Peng; He, Siyi; Gao, Junwei; Li, Jingwei; Fan, Xiaotang; Xiao, Ying-Bin
Abstract: Liver X receptors (LXRs) has been emerged as negative regulators of cardiomyocytic inflammation. The cellular process of autophagy is believed to play a protective role in myocardium during the inflammatory status. In this study, we investigated the role of LXRs agonist TO901317 (TO) on lipopolysaccharides (LPS)-induced myocardial inflammation and autophagy. The results showed that TO pretreatment significantly reduced the LPS-induced infiltration of inflammatory cells, elevation of NF-κB protein, TNF-α, and IL-6 mRNA levels in the myocardium. Moreover, LPS stimulated autophagy in neonatal mice heart, and this effect was further enhanced by TO pretreatment as evidenced by increased LC3-II/GAPDH ratio increment. Furthermore, TUNEL assay revealed LPS stimulation also increased the number of apoptotic cells in the myocardium, and the increment was inhibited by TO pretreatment. Our findings suggested that attenuation of inflammation and apoptosis, and enhancement of autophagy by TO may contribute to the protection of myocardium under inflammatory condition. Graphical abstract: : TO901317 pretreatment is associated with enhanced autophagy, attenuated inflammation and apoptosis in neonatal mouse heart after acute LPS challenge